Ratio between Abdominal Defect Size and Abdominal Circumference Measured Preoperatively May Predict Type of Closure in Neonates with Gastroschisis - Rajib Bora; Simmi K. Ratan; Anju Romina Bhalotra; Sujoy Neogi; Prafull Kumar; Gaurav Saxsena (Journal of Indian Association of Pediatric Surgeons)
Introduction: This study was undertaken to explore if abdominal anthropometric measurements and pressure parameters measured before closure can predict the choice of surgical procedure in neonates with gastroschisis. Materials and Methods: Twenty-two neonates presenting to our tertiary center with gastroschisis over 18 months were included. Abdominal anthropometric measurements such as defect circumference (DC), abdominal circumference (AC), abdominal height (H), anteroposterior diameter (APD), and abdominal volume (AV) were measured soon after induction and again before final closure. Simultaneously, peak inspiratory pressure (PIP) and intravesical pressure (IVP) were measured. A protocol of pressure increase of >20% from the baseline for Silo was followed. The data were analyzed segregating the subjects into two those requiring Silo (n = 16) and not requiring Silo (n = 6). Observation and Results: Non-Silo group did not differ from the Silo group for DC, AC, DC:AC ratio, Height, APD, and AV. Significant differences were noted between non-Silo and Silo groups in PIP (16 ± 1.9 vs. 12.88 ± 2.66) and IVP (1.83 ± 2.64 vs. 1.20 ± 2.08) preoperatively and pre-closure. DC:AC cut-off for predicting Silo was ≥0.31, with 73% sensitivity, and 50% specificity. DC:AC correlated positively with preoperative abdominal height, pre-closure AV, and abdominal height (P = 0.005, P = 0.008, and P = 0.007, respectively). Conclusions: Silo group had unfavorable abdominal anthropometric parameters as compared to non-Silo. DC:AC ratio which can be computed in a nursery setting and can be a promising variable to predict the type of closure for neonates with gastroschisis as it correlated with AV. A larger study is required to substantiate these conclusions.